A cucurbit[8]uril-based probe for the detection of the pesticide tricyclazole. (March 2022) - Wu, Heng; Zhao, Jie; Yang, Xi Nan; Yang, Dan; Chen, Li Xia; Redshaw, Carl; Yang, Li Guo; Tao, Zhu; Xiao, Xin
Abstract: A system comprising cucurbit[8]uril (Q[8]) and a fluorescent molecule (E)-1-(2-hydroxyethyl)-4-(4-hydroxystyryl)pyridin-1-ium bromide (HPy) has been utilized to construct a fluorescent probe that is capable of detecting the pesticide tricyclazole (TC). A variety of techniques including 1 H NMR spectroscopy together with fluorescence experiments have been employed to investigate the host-guest properties of the Q[8]/HPy system in aqueous solution. Results indicate that the system forms the stable2:1 inclusion complex HPy2 @Q[8], and that this inclusion complex imparts fluorescent quenching on HPy. The addition of a number of pesticides was found to have no obvious effect on the fluorescence, however on addition of tricycazole (TC), the fluorescence intensity underwent a dramatic enhancement. The linear relationship between the fluorescence intensity and the concentration of TC allowed for the facile detection of TC concentration in aqueous target solutions as well as in agricultural products. The detection limit was found to be 3.70 × 10 −8  mol L −1 . Graphical abstract: Image 1 Highlights: We report a fluorescent probe system for the highly selective and sensitive detection of the pesticide tricyclazole (TC). The encapsulation of HPy into Q [8] cavity can strongly quench the fluorescence emission because of charge-transfer. The linear relationship between the fluorescence intensity and the concentration of TC allowed for the facile detection of TC concentration in aqueous target solutions as well as in agricultural products.